PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII3 SMPN 3 SIAK KECIL PADA MATERI BANGUN RUANG SISI DATAR - Alinda Alinda; Atma Murni; Maimunah Maimunah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The background of this research is the result of learning mathematics of class student VIII3 SMP Negeri 3 Siak Kecil which is still under the minimum mastery criteria (MMC) with a persentage of 48, 15 % only 13 students from 27 students who achieve the minimum mastery criteria on the subject matter of the two variable linear equation system. The purpose of this research aims to improve the learning process and increase the student’s mathematics learning outcomes through the implementation of the Cooperative learning of Student Team Achievement Division (STAD) type. This type of research is the Classroom Action Research with two cycle, who conducted in class VIII3 SMP Negeri 3 Siak Kecil in the second semester of the 2018/2019 academic year. Research subject as many 27 students, consist of 14 boys and 13 girls. The research instrument consists of learning devices and instrument data collectors. Learning device used is Syllabus, Lesson Plan and Worksheet. The instrument data collector used in this research is the observation sheet and math achievement test. The observation sheet was analyzed whit descriptive qualitative while the test of mathematics learning outcomes was analyzed statistically. Based on deskriptive qualitative analiysis showed that implementation of learning process on cycle II had happened improvement from implementation on cycle I. Weakness on cycle I is improved on implementation cycle II according with planning of improvement after reflection cycle I. Number of students that reach MMC increase from basic score to daily test II. The number of students who reach Minimum Mastery Criteria on basic scor, daily test I and daily test II are respectively 13 person (48,15 %), 18 person (66,66 %) and 23 person (85,18%). Results of this research indicates that application of the Cooperative learning of STAD type can improve learning process and increase mathematics learning outcomes from the students at class VIII3 SMP Negeri 3 Siak Kecil the second semester academic years 2018/2019.Key Words: Math Learning outcomes, Cooperative Learning of STAD type,Classroom Action Research.